Agonist binding to the NMDA receptor drives movement of its cytoplasmic domain without ion flow - Kim Doré; Jonathan Aow; Roberto Malinow (2015)
The NMDA receptor (R) plays important roles in brain physiology and pathology as an ion channel. Here we examine the ion flow-independent coupling of agonist to the NMDAR cytoplasmic domain (cd). We measure FRET between fluorescently tagged cytoplasmic domains of GluN1 subunits of NMDARs expressed in neurons. Different neuronal compartments display varying levels of FRET, consistent with different NMDARcd conformations. Agonist binding drives a rapid and transient ion flow-independent reduction in FRET between GluN1 subunits within individual NMDARs. Intracellular infusion of an antibody targeting the GluN1 cytoplasmic domain blocks agonist-driven FRET changes in the absence of ion flow, supporting agonist-driven movement of the NMDARcd. These studies indicate that extracellular ligand binding to the NMDAR can transmit conformational information into the cell in the absence of ion flow.